Somatic mutations of the EGF receptor and their signal transducers affect the efficacy of EGF receptor-specific tyrosine kinase inhibitors - Gotoh, Noriko (e-Century Publishing Corporation, 2011)
Non-small cell lung cancer (NSCLC) is a major subtype of lung cancer that has been the most common and most fatal cancer worldwide. Gefitinib (Iressa™) and erlotinib (Tarceva™), specific tyrosine kinase inhibitors (TKI) for the epidermal growth factor receptor (EGFR), have been demonstrated to be effective for some NSCLC patients and are pioneering molecular-targeted drugs used in the clinic for cancer. Because many studies indicate that only some patient populations benefit from these drugs, there has been an urgent need to develop diagnostic methods to select appropriate patients for whom treatment with these drugs will be beneficial. Moreover, problems of acquired resistance after long-term treatment with the drugs have emerged. In this review, I summarize the current understanding of the EGFR-activated signal transduction pathway, which plays important roles in tumorigenesis, and of the molecular mechanisms that determine the sensitivity toward EGFR-TKI.